IDENTIFICATION OF KEY DETERMINANTS IMPACTING THE DURATION OF ORTHODONTIC TREATMENT - Nigmatova, I.M.; Ahmadi, Behnaz (Educational Research in Universal Sciences, 2023)
Orthodontics is one of the treatment methods to align the teeth. Due to the expansion of science in the field of dentistry and the arrangement of teeth, various orthodontic methods have been created. And there is a different treatment method for each type of abnormality. Clients and patients undergoing orthodontic treatment in most cases like their orthodontic period to be short. The purpose of this retrospective study was to identify the quantify the effect of factors that influence orthodontic treatment time.